A Contrastive Study of Walk Verb in English and Makassarese Language - Farah Fadilah; Machmoed, Hamzah A.; Sukmawaty (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
This paper aims to contrast sentences and interpretations of the meaning and the grammatical constructions of the verb walk in English under Dixon’s principle and Makassarese languages.The data from this study were taken from two sources. The English data was taken from the Corpus of Contemporary America English (COCA) while the Makassar language data was taken from the Mangkasara Dictionary. The data were collected and analyzed using a descriptive qualitative method design. The results of this study indicate that: 1) There is one walk verb in English and there are thirteen verbs in Makassaeese; 2) both of the language has similarities that can be implemented in intransitive and transitive verbs 3) The verb walk found in both languages has some similarities and differences in terms of sentence construction and interpretation of meaning. 4) Walk verb in Makassarese language produce seven pattern of the structure that are VP+ADV+NP, ADV+ADJ+NP+VP, ADV+NP+VP+NP, VP+NP+ADV+NP, ADJ.P+NP+ADV VP+NP, VP+NP+NP, VP+NP.